A Phase II, Open-Label Study of Lenalidomide and Dexamethasone Followed by Donor Lymphocyte Infusions in Relapsed Multiple Myeloma Following Upfront Allogeneic Stem Cell Transplant - Richard LeBlanc; Stéphanie Thiant; Rafik Terra; Imran Ahmad; Jean-Sébastien Claveau; Nadia Bambace; Léa Bernard; Sandra Cohen; Jean-Sébastien Delisle; Silvy Lachance; Thomas Kiss; Denis-Claude Roy; et al. (Current Oncology)
Background: To date, the only potential curative treatment for multiple myeloma (MM) remains allogeneic (allo) hematopoietic cell transplant (HCT), although, most patients will eventually relapse. In relapsed patients, donor lymphocyte infusions (DLIs) have been reported to control disease, but the optimal strategy prior to and doses of DLIs remain unclear. With this study (NCT03413800), we aimed to investigate the efficacy and toxicity of lenalidomide and dexamethasome (Len/Dex) followed by escalating pre-determined doses of DLIs in MM patients who relapsed after allo HCT. Methods: Patients aged 18–65 years with relapsed MM following upfront tandem autologous (auto)/allo HCT were eligible. Treatment consisted of six cycles of Len/Dex followed by three standardized doses of DLIs: 5 × 106 CD3+/kg, 1 × 107/kg and 5 × 107/kg every 6 weeks. Bone marrow minimal measurable disease (MRD) using flow cytometry (10−5) was performed at enrolment, then every 3 months for 2 years or until disease progression, in a subset of patients. The primary endpoint was efficacy as measured by progression-free survival (PFS) at 2 years following Len/Dex/DLIs. Secondary objectives were safety including GVHD, response including MRD status and overall survival (OS). Results: A total of 22 patients participated in this study, including 62% with high-risk cytogenetics. With a median follow-up of 5.3 years (range: 4.1–6.1), PFS and OS were 26.5% (95% CI: 10.4–45.9%) and 69.2% (95% CI: 43.3–85.1%), respectively. Overall, the best responses achieved post-Len/Dex + DLIs were complete remission in 9.1%, very good partial response in 50%, and progressive disease in 40.9%. Among the nine patients tested for MRD, only two achieved a negative status after receiving DLIs. Six patients died, all due to disease progression. No acute GVHD was observed after DLIs. We report a very low incidence of moderate/severe chronic GVHD of 18.2% with no need for systemic immunosuppressants one year after diagnosis. No unexpected adverse events were observed. Interestingly, a positive correlation between response to Len/Dex re-induction and response to DLIs was found (p = 0.0032). Conclusions: Our findings suggest that Len/Dex/DLIs in second line treatment after upfront tandem auto/allo HCT in relapsed MM patients remains feasible and safe. With a potential correlation between induction chemotherapy and DLI responses, more potent induction regimens together with higher doses of DLIs should be considered in the future.